Time-restricted feeding modulates the DNA methylation landscape, attenuates hallmark neuropathology and cognitive impairment in a mouse model of vascular dementia - Selvaraji, Sharmelee (2022)
Objective: Vascular dementia (VaD) is the second most common cause of dementia worldwide. The increasing contribution of lifestyle-associated risk factors to VaD has pointed towards gene-environment interactions (i.e. epigenetics). This study thus aims to investigate the DNA methylation landscape in a chronic cerebral hypoperfusion (CCH) mouse model of VaD. As a nexus between the gene-environment interaction, intermittent fasting (IF) was introduced as a prophylactic intervention. Methods: Bilateral common carotid artery stenosis (BCAS) was used to induce CCH by placing micro-coils of 0.18 mm in each common carotid artery of the mice. The coils were left in the mice for 7, 15 and 30 days to study temporal differences. IF was introduced for 16 h daily for 4 months prior to BCAS. Reduced Representation Bisulfite Sequencing (RRBS) was used to study the DNA methylation landscape. Cognitive impairment was measured using Barnes Maze Test. White matter lesions (WML) and neuronal loss were measured using Luxol fast blue staining and cresyl violet staining respectively. Results: IF mice subjected to CCH displayed significantly better cognitive learning ability and memory, improved neuropathological alterations with reduced WMLs and neuronal loss. Modulation of DNA methylation patterns in the cortex of AL CCH mice was re-modelled and signs of reversal was observed in IF CCH mice across all three timepoints. Conclusions: These findings provide an understanding of how IF may protect the brain against damage caused by CCH and show promise in offering potential beneficial effects in mitigating the neuropathology and cognitive deficits in VaD.